THE IMPORTANCE OF ISLAMIC ATMOSPHERE IN THE RETAIL BUSINESS A NEW ALTERNATIVE IN MANAGING RETAIL BUSINESS CASE STUDIES ON SYARIAH MINI MARKET: SYAR'E MART UII - Khusniyah Purwani; Joko Susilo (Asian Journal of Innovation and Entrepreneurship, 2012)
This paper aims to demonstrate a small- scale studies that explore the importance of retail Islamic atmosphere and contributed substantial in the success of the retail business. Especially looking for models or other forms of modern retail management based on syariah or Islamic rule. This paper also explores the relevance of the Islamic atmosphere of retail success. In this paper, we present case studies on UII Syariah Mini Market-Syar'e Mart that can describe the successes and try to draw conclusions by qualitative descriptive analysis of this case study. The findings show that the Islamic model of retail becomes a new alternative in managing the retail business. The concept of retail syariah has the opportunity to grow and succeed. That atmosphere was exciting retail syariah/ important than conventional retail atmosphere. Islamic retail atmosphere be one of the new tool in the retail industry. Islamic studies show that retail in the retail industry has contributed a new alternative in managing, developing and improving the retail industry. Keyword: Syariah mini market, Syar'e Mart, the retail atmosphere of syariah, marketing